Paper planes - Wood, Jennie (Comic book author) (Maverick for Mad Cave Comics Inc., published by Mad Cave Studios, Inc., 2023)
After a life altering incident, Dylan and Leighton are sent to a summer camp for troubled youth. Can Dylan and Leighton save their friendship and protect their future while trying to survive camp?